Design a Comprehensive Evaluation and Noval Approaches from Natural Source of Microspheres from Anti-hyperlipidimic Drug - Venkateswarlu, Bendi Sri; Chandira, Rajappa Margret; Pethappachetty, Palanisamy; Raffic, Naveeth (Asian Journal of Biological and Life Sciences)
To deliver Atorvastatin orally, researchers developed bioadhesive controlled release microspheres utilising sodium alginate, guar gum, locust bean gum, and xanthan gum as copolymers. Atorvastatin microspheres may be effectively made using the ionotropic gelation process and the ionic cross-linking approach. Other procedures make use of higher volumes of organic solvents, which are more expensive and dangerous due to the risk of explosion, air pollution, toxicity, and the difficulty in removing all residues of organic solvent. The micrometric investigations showed that the produced microspheres had a mean particle size of 512-903m, which is acceptable for oral administration as bioadhesive controlled release microspheres. Percent yield, percent drug entrapment efficiency, particle size and swelling and mucoadhesion all increased as a result of an increase in polymer concentration. Microspheres of Atorvastatin utilising sodium alginate together with guar gum as a copolymer stuck to the mucus more strongly than those using sodium alginate combined with locust bean gum and xanthan gum as copolymers.
Keywords: Atorvastatin; Guar gum; Microspheres; Percentage of swelling and percentage of mucoadhesion; Xanthan gum